Longitudinal study on poultry rearing in Manikganj: a preliminary assessment for the first quarter - Mallick, N.C. (BRAC, 2019)
Vulnerable Group Development (VGD) program sponsored by a number of donors aimed at supplementing nutritional level and assisting the process of attaining self reliance by the rural destitute womenfolk. The womenfolk receive supply of wheat ration of 31.25 kg per month for 2 years period and the programme has long been implemented by the government. But lack of proper administration and supervision of the government turned the program purely a relief program. Bangladesh Rural Advancement Committee (BRAC) envisaged this monthly wheat ration as an input, which if associated with other services, could be transformed to an effective program for poverty alleviation and planned to .impart the . VGD wheat receivers training and production skills on poultry keeping so that some sort of income generating avenue become open for them. Initially in 1985, Integrated Development Program (IDP), Manikganj started a pilot program in cooperation with the World Food Program (WFP) and its success led BRAC to launch an independent program in late 1987, known as "Income Generation for Vulnerable Group Development Program ( IGVGDP) ". The present study is an evaluation of the program's prime objective of income achievement. The findings can be summarised as in the following: The total income achievement in the program study population rearing HYV is negative while it is positive for those in the nonintervened group rearing traditional variety (control) under analysis based on estimated feed cost. When analysis is made on the basis of reported feed cost the situation is really grave. The hatching rate and mortality rate of chicks both favour the control group compared to the program group. It means that, hatching rate is lower and mortality rate of chicks is higher for the program group. The performance level of VGD wheat beneficiaries can no way be regarded as better than the non-beneficiaries . - Abnormal loss to few program respondents could be attributed to the deaths of aged poultry birds known as pullets resulting in an absolute loss of original investment. Size of poultry farm seems to be somewhat positively associated with profit earned by the VGD wheat beneficiaries. The present evaluation is a preliminary attempt to assess the existing situation -of the program which requires proper attention and requisite improvements.